Sistem Rekomendasi Film Menggunakan Integrated Kohonen K-Means clustering - Joshua Maximillian; Henry Novianus Palit; Alvin Nathaniel Tjondrowiguno (Jurnal Infra, 2020)
With the development of the film industry, more and more films can be watched. But because there are too many films that can be watched that cause users to be confused in finding films that match what they like. So there is a movie recommendation system to help user. The movie recommendation system itself has various ways to produce movie recommendations that users might like.The movie recommendation system using Integrated Kohonen K-Means Clustering is one of the Data Mining methods that can be used in recommending films. Intergrated Kohonen K-Means Clustering compared to Kohonen Self Organizing Maps, and also K-Means Clustering in recommending films.According to the result of Integrated Kohonen K-Means Clustering to know how many K cluster that is optimal for K-Means Clustering use the Elbow Method. To know how good the cluster you produce use Silhouette Coefficient and the score -0.389 for the Integrated Kohonen K-Means Clustering. The Mean Reciprocal Rank produced by Integrated Kohonen K-Means Clustering which score is 0.362 is better than K-Means Clustering which score is 0.003 and Kohonen Self Organizing Maps which score is 0.002.